Aluminum adsorbing material for extracting lithium from salt lake as well as preparation method and application of aluminum adsorbing material
By using a composite of aluminum-based adsorbent powder and polymeric materials as salt lake lithium extraction materials, the problems of high equipment maintenance costs and low lithium extraction efficiency in the existing technology are solved, and high efficiency and economical lithium extraction are achieved in realization Ion extraction effect.
Patent Information
- Application Number
- CN202411817465.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-02-11
AI Technical Summary
The existing salt lake lithium extraction technology has problems such as high maintenance costs, high investment costs for auxiliary materials, low efficiency of lithium extraction of low-concentration brine, difficulty in controlling side reactions, and large freshwater consumption of membrane separation methods.
The composite of aluminum-based adsorbent powder and polymeric material is used as the salt lake lithium-enhancing aluminum-based adsorbent material. The aluminum-based adsorbent powder is prepared through complex precipitation reaction, and the polymeric material is hot melted to form porous and loose The particulate material is used for adsorption and elution of lithium ions in brine.
A single adsorption of lithium in different types of salt lakes has been achieved, with a large adsorption amount, which can effectively separate other calcium, maflora, boron plasma in brine, and preferentially extract lithium ions. The extracted lithium salt has a smaller loss after eluting and concentration, and the yield is relatively high. High, stable structure, long cycle life, and resistant to salt water erosion.
Smart Images

Figure CN119406387A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of salt lake lithium extraction materials, and in particular to a salt lake lithium extraction aluminum series adsorption material and a preparation method and application thereof. Background Art
[0002] With the continuous increase in the use of lithium-ion batteries in new energy electric vehicles, smart electronic products, power grid energy storage and electric machinery, the demand for lithium resources is also growing rapidly. However, China's lithium resources only account for about 7% of the world's total reserves, and 80% of my country's lithium resources are distributed in lithium-containing salt lake areas in western China, such as Qinghai, Tibet, and Xinjiang. The green development, comprehensive utilization, and single extraction of lithium salts in salt lakes require high technology. Effectively utilizing various metal ions in salt lakes while protecting the ecological environment is the current research direction. The relative content of potassium, calcium, magnesium, sodium, boron, carbonate, sulfate, and chloride ions in salt lake brine is relatively high, and the relatively low content of lithium ions makes it difficult to extract lithium. The main processes for extracting lithium ions include extraction, precipitation, electrochemical, membrane + adsorption, etc.
[0003] The extraction process requires the extraction or precipitation of each metal ion step by step. In the traditional process, the more impurity removal steps there are, the greater the ion process loss, and the final separation and purification of the lithium salt metal yield is also lower. The extraction method has high requirements for process equipment, which makes the equipment maintenance cost high. In addition, the input cost of auxiliary materials for the extraction method is relatively large, and the solvent also needs to be properly handled.
[0004] The electrochemical process mainly enriches lithium ions in brine based on the applied voltage of positive and negative electrodes. It is suitable for salt lakes with high content of various ions in the brine. The efficiency of lithium extraction from low-concentration brine is low, and side reactions are difficult to control. The processing costs of positive and negative electrodes are relatively high.
[0005] Lithium extraction from salt lakes must not only meet the requirements of efficient lithium extraction, recycling, economy and environmental protection, but also be suitable for low-concentration brine and resistant to salt water erosion. Currently, various lithium extraction processes mainly reduce the content of various ions in brine. Over time, the salt content of brine will gradually decrease, and the cost of electrochemical methods will also increase. Priority is given to membrane method + adsorption method, which has relatively low equipment investment, and the technology is constantly improving, constantly breaking through the adsorption capacity of lithium ions in low-concentration brine.
[0006] At present, the main methods for extracting lithium from salt lakes are membrane separation and electrochemical deintercalation. However, these methods have certain disadvantages. For example, the membrane separation method consumes a lot of fresh water, which is limited in salt lake mining areas where fresh water resources are scarce. In addition, the Li in brine is + and Na + / K + It is difficult to separate by membrane, so it is necessary to first separate the Na + and K +Removal by evaporation results in a large loss of lithium; electrochemical deintercalation lithium extraction technology is only applicable to low-grade salt lake brine systems, and has problems such as low lithium exchange capacity, poor electrode cycle performance, and high energy consumption of the electrode system. These shortcomings greatly limit their application. Summary of the invention
[0007] The purpose of the present invention is to overcome the defects of the above-mentioned prior art and to provide a salt lake lithium extraction aluminum adsorption material and a preparation method and application thereof.
[0008] The invention provides an aluminum-based adsorption material for lithium extraction from salt lakes. The aluminum-based adsorption material for lithium extraction from salt lakes is a composite of aluminum-based adsorbent powder and a polymer material, wherein: the composition of the aluminum-based adsorbent powder is LiXAl(OH)3·nH2O, X is at least one of Cl, SO4, CO3, PO4, and NO3, and the mass ratio of the aluminum-based adsorbent powder to the polymer material is 1.0:(0.5-1.0).
[0009] The present invention also provides a method for preparing the above-mentioned aluminum-based adsorbent material for lithium extraction from salt lakes, which comprises: mixing a mixed salt solution of aluminum and lithium with a complexing agent solution to carry out a complex precipitation reaction, obtaining an aluminum-based adsorbent powder after treatment, mixing the aluminum-based adsorbent powder with a polymer material and then hot-melting it into a fluid state, then extruding or granulating it with a mold, and using an eluent to circulate and elute lithium ions to obtain the aluminum-based adsorbent material for lithium extraction from salt lakes.
[0010] The present invention also provides the above-mentioned aluminum-based adsorption material for lithium extraction from salt lakes or the use of the aluminum-based adsorption material for lithium extraction from salt lakes prepared by the above-mentioned preparation method in lithium extraction from salt lakes.
[0011] The present invention has the following beneficial effects: The present invention provides an aluminum-based adsorption material for lithium extraction from salt lakes, and a preparation method and application thereof. The aluminum-based adsorption material for lithium extraction from salt lakes provided by the present invention has a single adsorption property for lithium in different types of salt lakes and a large adsorption capacity, can effectively separate other calcium, magnesium, iron, boron and other ions in brine, and preferentially extract lithium ions. The extracted lithium salt has a small loss after elution and concentration, and a high yield. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0013] Figure 1 A flow chart for the preparation of aluminum-based adsorption materials for lithium extraction from salt lakes; Figure 2 This is a SEM image of the aluminum-based adsorbent prepared in Example 1 of the present invention, and Figures a, b, c and d are SEM images at different magnifications; Figure 3 This is a schematic diagram of the device structure for the adsorption and elution processes of aluminum-based adsorption materials for lithium extraction from salt lakes; Description of the drawings: U-shaped tube-100, bracket-200, union and blue filter-300, pure water flushing port-400, brine filling port-500, eluent filling port-600, elution tank-700, brine tank-800, lithium-containing wastewater discharge port-900, brine discharge port-1000, water pump-1100, brine pump-1200. DETAILED DESCRIPTION
[0014] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0015] The following is a detailed description of an aluminum-based adsorption material for lithium extraction from salt lakes and its preparation method and application provided in an embodiment of the present invention.
[0016] In the first aspect, an embodiment of the present invention provides an aluminum-based adsorbent material for lithium extraction from salt lakes. The aluminum-based adsorbent material for lithium extraction from salt lakes is a composite of an aluminum-based adsorbent powder and a polymer material, wherein: the composition of the aluminum-based adsorbent powder is LiXAl(OH)3·nH2O, X is at least one of Cl, SO4, CO3, PO4, and NO3, and the mass ratio of the aluminum-based adsorbent powder to the polymer material is 1.0:(0.5-1.0).
[0017] The aluminum-based adsorption material for lithium extraction from salt lakes provided in the embodiment of the present invention is a composite of aluminum-based adsorbent powder and high molecular polymer material. The aluminum-based adsorption material for lithium extraction from salt lakes has a single adsorption property for lithium in lithium chloride salt lakes, lithium sulfate salt lakes, and lithium sulfate salt lakes, and can effectively separate other calcium, magnesium, iron, and boron ions in brine, and can preferentially extract lithium ions. The extracted lithium salt has a small loss after elution and concentration, and a high yield. In addition, the aluminum-based adsorption material for lithium extraction from salt lakes has a larger adsorption capacity than traditional aluminum adsorbents, and the unit mass of the aluminum-based adsorption material for lithium extraction from salt lakes has a large mass of adsorbed lithium ions. It also has the advantages of stable structure, long cycle life, and resistance to salt water erosion.
[0018] In an optional embodiment, the polymer material is a thermoplastic material, and the thermoplastic material includes at least one of PP, PPS, PVC, PVDF, resin, glycolipid, phenolic resin, urea-formaldehyde resin, melamine resin, unsaturated polyester resin, epoxy resin, silicone resin, and polyurethane.
[0019] In an optional embodiment, the specific surface area of the aluminum adsorbent powder is 30 m 2 / g-100m 2 / g, tap density is 0.8g / cm 3 -1.2g / cm 3 .
[0020] In an optional embodiment, the lithium adsorption capacity of the aluminum-based adsorption material extracted from salt lake is 4.0 mg / g-6.0 mg / g, and the salt lake type includes at least one of lithium chloride salt lake, lithium sulfate salt lake, and lithium sulfate salt lake.
[0021] The embodiment of the present invention provides an aluminum-based adsorption material for lithium extraction from salt lakes. The aluminum-based adsorption material for lithium extraction from salt lakes is a composite of aluminum-based adsorbent powder and thermoplastic material, wherein the specific surface area of the aluminum-based adsorbent powder is 30 m 2 / g-100m 2 / g, tap density is 0.8g / cm 3 -1.2g / cm 3 . It is an aluminum-based adsorbent powder with both high specific surface area and low tap density, which is a decisive factor in the adsorption performance of aluminum-based adsorbent materials for lithium extraction from salt lakes. The adsorption performance is doubled compared to the products currently prepared. The theoretical adsorption capacity of 1 ton of granular products can reach 10kg of lithium ions. In actual tests, the adsorption capacity of 400ppm lithium-containing brine reached 4kg-6kg of lithium ions, and the adsorption rate was about 50%. The adsorption time of the test process is within 4 hours to 8 hours, and the elution time can also be controlled within 8 hours. The entire adsorption cycle is about 16 hours. The brine flow rate in the adsorption process is set at 0.5 times to 1 times the volume of the particle filling tower, and the eluent flow rate in the elution process is set at 1 times to 2 times the volume of the particle filling tower, which meets the requirements of low flow rate adsorption and high flow rate elution. This adsorption-elution method has a large adsorption capacity, a short adsorption and elution cycle, and high adsorption efficiency.
[0022] The aluminum-based adsorption material for lithium extraction from salt lakes provided in the embodiment of the present invention has an aluminum-based adsorbent powder composition of LiXAl(OH)3·nH2O, where X is at least one of Cl, SO4, CO3, PO4, and NO3, and can be applied to different types of lithium extraction products from salt lakes. The aluminum-based adsorption material for lithium extraction from salt lakes provided has excellent performance, stable structure, high adsorption efficiency, large adsorption capacity, and long cycle life, and has good practicality and application prospects.
[0023] In the second aspect, an embodiment of the present invention also provides a method for preparing the above-mentioned aluminum-based adsorbent material for lithium extraction from salt lakes, which comprises: mixing a mixed salt solution of aluminum and lithium and a complexing agent solution to carry out a complex precipitation reaction, obtaining an aluminum-based adsorbent powder after treatment, mixing the aluminum-based adsorbent powder with a polymer material and then hot-melting it into a fluid state, and then extruding or granulating it into molds, and using an eluent to circulate and elute lithium ions to obtain the aluminum-based adsorbent material for lithium extraction from salt lakes.
[0024] In an optional embodiment, the preparation of aluminum-based adsorbent powder includes: adding a mixed salt solution of aluminum salt and lithium salt to a reactor, starting stirring and heating, introducing compressed air with a pressure of 0.2MPa-0.4MPa and a flow rate of 1 / 30-1 / 10 of the volume of the reactor to the bottom of the mixed salt solution, and then continuously and constantly introducing the complexing agent solution into the reactor for precipitation reaction, controlling the flow rate of the complexing agent solution to 1 / 30-1 / 10 of the volume of the reactor, controlling the pH at 1.0-4.0 in the early stage of the precipitation reaction, controlling the pH at 4-8 in the middle stage, and controlling the pH at 8-12 in the late stage, adding a pH regulator to adjust the pH during the pH adjustment process, and obtaining a slurry after the precipitation reaction is completed, wherein: The aluminum salt includes at least one of aluminum sulfate, aluminum carbonate, aluminum chloride, aluminum silicate, and aluminum nitrate; the lithium salt includes at least one of lithium sulfate, lithium carbonate, and lithium chloride; the complexing agent includes at least one of ammonia water, urea, and sodium hydroxide; and the pH adjusting agent includes at least one of dilute sulfuric acid, dilute hydrochloric acid, dilute nitric acid, and dilute alkali; The total concentration of aluminum and lithium metal ions in the mixed salt solution is 1.0 mol / L-5.0 mol / L, and the proportion of metallic lithium in the metal ions is 20%-50%. The stirring speed of the mixed salt solution is 100 rpm-300 rpm, the heating temperature is 70°C-90°C, the concentration of the complexing agent solution is 10%-20%, the amount of metal ion substance in the mixed salt solution: the amount of complexing agent substance is 1 mol: (5-15) mol, and the concentration of the pH adjuster is 10%-30%.
[0025] The embodiment of the present invention also provides a method for preparing the above-mentioned aluminum-based adsorbent for lithium extraction from salt lakes. In the preparation process of the aluminum-based adsorbent, aluminum salt and lithium salt are preferentially configured into a mixed salt solution of a certain proportion and concentration, compressed air is introduced, and then a complexing agent solution is slowly and continuously introduced from the bottom of the reactor for complexation and precipitation. Compared with the traditional "one-pot" method (i.e., all materials are added to the reactor at one time for reaction), the structure of the prepared aluminum-based adsorbent is more stable. In addition, ammonia water is preferentially used as a precipitation complexing agent during the precipitation process, and the reaction rate is slower than that of sodium hydroxide, and the crystal structure of the product is stable, so that a high specific surface area and low tap density aluminum-based adsorbent for lithium extraction from salt lakes can be obtained. And in the preparation process, excessive ammonia water is used for complexation precipitation, and the hydroxide in the ammonia water participates in the precipitation reaction, and the ammonium ions in part of the ammonia water play a complexing role, slowing down the reaction rate of the system, and ensuring the stability of the crystal structure of the aluminum-based adsorbent. The by-product ammonium salt and excess ammonia water can be recycled and reused through the mother liquor washing water, and the ammonia water recycling can be achieved by using simple equipment such as an ammonia evaporation tower, thereby reducing the processing cost of lithium adsorbent preparation enterprises. The lithium ions eluted from the cycle are concentrated by membrane treatment and lithium salts are obtained after precipitation, which can be reused and reduce the cost of raw materials.
[0026] The aluminum-based adsorption material for lithium extraction from salt lakes prepared by the method provided in the embodiment of the present invention has strong compatibility, can meet the needs of different types of downstream salt lake lithium extraction processes, and can also break my country's dependence on lithium salt imports, thereby reducing the impact of the international environment on the market and prices of lithium salts and the battery industry chain.
[0027] It is worth noting that the embodiment of the present invention also provides a method for preparing the above-mentioned aluminum-based adsorbent material for lithium extraction from salt lakes. The composition of the aluminum-based adsorbent powder is LiXAl(OH)3·nH2O, where X is at least one of Cl, SO4, CO3, PO4, and NO3. The aluminum-based adsorbent powder with the above composition can be used to prepare products suitable for lithium extraction from salt lakes of different types. Alternatively, in the preparation stage of the granular material, two or more materials of the chloride-type, carbonate-type, sulfuric acid-type, and nitric acid-type powder precursor materials are mixed in proportion, and then mixed with thermoplastic materials for injection molding. The aluminum-based adsorbent material for lithium extraction from salt lakes is compatible with different salt lakes such as chloride-type, sulfuric acid-type, and carbonate-type salt lakes. At the same time, the aluminum-based adsorbent is coated with thermoplastic materials, is resistant to acid, alkali, and salt water erosion, and has high recycling performance.
[0028] In an optional embodiment, the method further includes: aging the slurry obtained by the reaction for 4h-6h, then washing with warm water at 40℃-60℃ until it becomes neutral, drying at 80℃-120℃ until the moisture content of the material is ≤40%, and then grinding the dried material to a maximum particle size of ≤50um to obtain an aluminum-based adsorbent powder.
[0029] In an optional embodiment, the preparation of aluminum-based adsorbent materials for lithium extraction from salt lakes includes: mixing aluminum-based adsorbent powder and high molecular polymer material in a mass ratio of 1.0:(0.5-1.0) to obtain a mixed material, and then introducing compressed air at a pressure of 0.2MPa-0.4MPa, a temperature of 80°C-120°C, and a flow rate of 1 / 20-1 / 10 of the volume of each batch of the mixed material into the mixed material, and then hot-melting at ≤300°C to obtain a fluid material, and then extruding and granulating the fluid material to obtain a porous and loose granular material, and cyclically eluting the porous and loose granular material with an eluent to remove lithium ions, to obtain the aluminum-based adsorbent material for lithium extraction from salt lakes.
[0030] The traditional granulation process preferentially dissolves polymer materials, for example, using organic solvents such as chloroform, acetic acid, dichloromethane, phenol, dimethyl sulfoxide, dimethylformamide, citric acid, etc. to dissolve PP, PPS, PVC, PVDF, resins, glycolipids, etc., and then adding powder materials for extrusion molding or water hardening molding. The preparation method of aluminum-based adsorbent materials for lithium extraction from salt lakes provided in an embodiment of the present invention comprises: mixing aluminum-based adsorbent powder with thermoplastic material and then hot-melting it into a fluid state, and using a granulation process to granulate the mixed hot-melt fluid material, which saves polymer organic solvents compared to traditional water-based granulation and reduces additional raw materials in the granulation process.
[0031] At the same time, the solution provided by the embodiment of the present invention can mix one or more powder materials in the mixing process of aluminum-based adsorbent powder and polymer materials, breaking through the single application environment of granular materials. Compressed air is introduced into the hot-melt process of the mixed materials, and polymer materials such as thermoplastic materials coat the aluminum-based adsorbent to form porous and loose granular materials, which can efficiently extract lithium ions from brine and meet the adsorption and extraction of low-concentration lithium-containing brine, and the aluminum-based adsorbent materials for lithium extraction from salt lakes can be recycled and reused. The aluminum-based adsorbent materials for lithium extraction from salt lakes have a stable structure, a large specific surface area, and high adsorption performance. At the same time, in the process of preparing aluminum-based adsorbent materials for lithium extraction from salt lakes, key raw materials such as ammonia water and lithium salts can also be collected and recycled, the preparation process is simple, and the production cost is also low. It is expected to be widely used in lithium extraction from salt lakes.
[0032] In a third aspect, an embodiment of the present invention further provides the above-mentioned aluminum-based adsorption material for lithium extraction from salt lakes or the use of the aluminum-based adsorption material for lithium extraction from salt lakes prepared by the above-mentioned preparation method in lithium extraction from salt lakes.
[0033] In an optional embodiment, during the lithium extraction adsorption process from the salt lake, the brine flow rate is 0.5 to 1 times the filling volume of the aluminum-based adsorption material for lithium extraction from the salt lake, and the eluent flow rate during the elution process is 1 to 2 times the volume of the tower filled with the aluminum-based adsorption material for lithium extraction from the salt lake.
[0034] The schematic diagram of the device structure for the adsorption and elution process of aluminum-based adsorption materials for lithium extraction from salt lakes is shown in the figure. Figure 3 As shown, the working process is as follows: the prepared granular product is filled into the U-shaped tube 100, the mouth of the U-shaped tube 100 is provided with a flexible joint and a blue filter 300, the U-shaped tube 100 is placed on the bracket 200, the eluent (pure water) is added into the elution tank 700 from the eluent filling port 600, the water pump 1100 is turned on, and the granular product in the U-shaped tube 100 is circulated and eluted with the eluent (pure water), the lithium-containing waste water is discharged from the lithium-containing waste water discharge port 900, and the eluent (pure water) is added into the elution tank 700 again for standby use. After the elution of the granular product is completed, salt lake brine is added to the brine tank 800 from the brine filling port 500, and the brine pump 1200 is turned on to transport the brine to the U-shaped tube 100. The eluted granular product is used to circulate and adsorb lithium ions in the brine. After a period of time, the adsorption is completed, and then the valve is switched to the eluent (pure water) in the elution tank 700 for elution. In this way, the adsorption amount of lithium in the brine by the granular product can be accurately detected. After adsorption, the remaining brine is discharged from the brine discharge port 1000. There are two methods for detecting the adsorption amount of lithium ions in the brine by the granular product. The first is to detect the remaining lithium content in the brine, and the second is to detect the lithium content in the eluent.
[0035] The aluminum-based adsorption material for lithium extraction from salt lakes provided in the embodiment of the present invention is applied to lithium extraction from salt lakes, has no pollution to the salt lake environment, and the aluminum-based adsorption material for lithium extraction from salt lakes itself does not contain organic solvents, and the loss of thermoplastic materials is low. In addition, when the aluminum-based adsorption material for lithium extraction from salt lakes provided in the embodiment of the present invention is applied to lithium extraction from salt lakes, the adsorption and elution efficiency is high, and a small amount of fresh water (pure water) at room temperature can be used for cyclic elution. After the eluted lithium salt solution is concentrated, the pure water can be recycled, and the demand for fresh water and groundwater is low.
[0036] As can be seen from the above, the embodiment of the present invention provides a salt lake lithium extraction aluminum adsorption material and its preparation method and application. The salt lake lithium extraction aluminum adsorption material provided by the embodiment of the present invention has a single adsorption property for lithium in lithium chloride salt lake, lithium sulfate salt lake, and lithium sulfate salt lake, can effectively separate other calcium magnesium iron boron ions in brine, can preferentially extract lithium ions, and the extracted lithium salt is less lost after elution and concentration, and has a high yield. The salt lake lithium extraction aluminum adsorption material provided by the embodiment of the present invention has high adsorption efficiency. The salt lake lithium extraction aluminum adsorption material is filled into a container, adsorbed at a low flow rate, eluted at a high flow rate, and the entire cycle is short, which can realize continuous automated production of downstream enterprises. The salt lake lithium extraction aluminum adsorption material provided by the embodiment of the present invention has a larger adsorption capacity than traditional aluminum adsorbents, and the unit mass of the salt lake lithium extraction aluminum adsorption material has a large mass of lithium ions adsorbed. After testing, the adsorption capacity in brine containing 400ppm of lithium reaches 4.0mg / g-6.0mg / g. The salt lake lithium extraction aluminum adsorption material provided by the embodiment of the present invention has a stable structure, a long cycle life, and is resistant to salt water erosion.
[0037] The present invention will be further described below in conjunction with the embodiments.
[0038] Example 1 A method for preparing aluminum-based adsorption materials for lithium extraction from salt lakes, see Figure 1 , including the following steps: 1. Raw materials and equipment preparation Aluminum sulfate, lithium sulfate, ammonia water and polypropylene are used as raw materials. 100L reactor, feeding pump, small centrifuge, screening machine, mixer, hot melt injection molding machine, PPH storage tank and other equipment are used.
[0039] 2. Ingredients 15.00 L of aluminum sulfate solution with a metal ion concentration of 1.85 mol / L and 2.55 L of lithium sulfate solution with a metal ion concentration of 3.60 mol / L were prepared. After the two metal salt solutions were mixed, 13.27 L of pure water was added to prepare 30.82 L of aluminum sulfate and lithium sulfate mixed salt solution with a molar ratio of aluminum and lithium metal ions of 75%:25% and a total metal ion concentration of 1.2 mol / L (mass concentration: 1.2×21.97=26.4 g / L).
[0040] 3. Reaction Take 30L of qualified aluminum-lithium mixed salt solution and add it to the reactor, turn on the stirring at 150rpm, set the temperature to 70℃, and after the temperature reaches 70℃, introduce compressed air with a pressure of 0.3Mpa and a flow rate of 5L / h. At the same time, use a peristaltic pump to pass 20% ammonia water into the reactor at a flow rate of 5L / h. The ammonia water addition time is 6 hours, and the total amount of ammonia water added is 30L. The whole reaction is an exothermic process, during which the online pH gradually increases from 2.1 to 10.9. After adding ammonia water, adjust the pH. If the pH is not reached, add 10% sodium hydroxide to adjust it appropriately. The start time of the entire reaction starts from the addition of ammonia water. A white precipitate is produced after the addition of ammonia is completed. The stirring is increased to 180rpm, and the compressed air flow rate is not adjusted. Continue the reaction for 18 hours to obtain a slurry. After the reaction is completed, turn off the stirring, turn off the heating, and turn off the compressed air. The reaction equation is as follows: Al2(SO4)3+0.3Li2SO4+6NH3·H2O→0.3Li2SO4·2Al(OH)3·nH2O↓+2(NH4)2SO4(n=6).
[0041] 4. Aging The slurry obtained from the above reaction was transferred to an aging tank and aged for 4 hours.
[0042] 5. Washing The aged slurry is added into a centrifuge to remove the mother liquor, and then washed continuously at high speed with 45°C warm pure water until the pH of the washing water is detected to be below 8.
[0043] 6. Drying Put the washed qualified materials into the oven for drying at a temperature of 100°C for 6-10 hours.
[0044] 7. Grinding The dried material was poured into a ball mill and ground until there was no agglomerate. After grinding, 5 kg of solid particles (with a water content of about 40%, including crystal water) were obtained.
[0045] 8. Mixing hot melt molding Take 4kg of polypropylene granules and 5kg of the above-ground powder, mix thoroughly and put them into a hot melt injection molding machine, melt them into a fluid state at 250℃. Pass compressed air through the extrusion hole to extrude them into cylindrical strips, and cut them into granular materials of Ф3mm×4mm.
[0046] 9. Product indicators and performance testing The lithium aluminum ratio of the aluminum adsorbent powder prepared by this method is 1 mol:3 mol. Figure 2 As shown in the figure, it can be seen that the aluminum adsorbent powder is spherical or quasi-spherical as a whole, and some particles are bud-shaped, with a specific surface area of 76.2m 2 / g, tap density is 0.82g / cm 3 Using 400ppm lithium-containing brine for testing, the minimum adsorption of the granular material is 4.3mg / g, and the maximum adsorption is 5.8mg / g. Figure 3 As shown, by directly simulating the use of salt lake brine, the lithium content is detected by ICP directly using the eluted liquid. Currently, the adsorbent developed and prepared by the company has an adsorption capacity of 2mg / g-4mg / g.
[0047] Example 2 1. Raw materials and equipment preparation Same as Example 1.
[0048] 2. Ingredients 15.00 L of aluminum sulfate solution with a metal ion concentration of 3.7 mol / L and 2.55 L of lithium sulfate solution with a metal ion concentration of 7.2 mol / L were prepared. After the two metal salt solutions were mixed, 13.27 L of pure water was added to prepare 30.82 L of aluminum sulfate and lithium sulfate mixed salt solution with a molar ratio of aluminum to lithium of 75%:25% and a total metal ion concentration of 2.4 mol / L (mass concentration: 2.4×21.97=52.7 g / L).
[0049] 3. Reaction Take 30L of qualified aluminum-lithium mixed salt solution and add it to the reactor, turn on the stirring at 180rpm, set the temperature to 70℃, and after the temperature reaches 70℃, introduce compressed air with a pressure of 0.3Mpa and a flow rate of 5L / h. At the same time, use a peristaltic pump to pass 20% ammonia water into the reactor at a flow rate of 5L / h. The time for adding ammonia water is 6 hours, and the total amount of ammonia water added is 30L. The whole reaction is an exothermic process, during which the online pH gradually increases from 2.5 to 10.6. After adding ammonia water, adjust the pH, switch the peristaltic pump to supplement 20% concentration of sodium hydroxide at a flow rate of 5L / h, and the time for this supplementary addition of sodium hydroxide is 1h. The start time of the entire reaction starts from the addition of ammonia water. A white precipitate is produced after adding ammonia. The stirring is increased to 240rpm, and the compressed air flow rate is not adjusted. Continue the reaction for 18 hours to obtain a slurry. After the reaction is completed, turn off the stirring, turn off the heating, and turn off the compressed air. The reaction equation is as follows: Al2(SO4)3+0.3Li2SO4+3NH3·H2O+3Na(OH)→0.3Li2SO4·2Al(OH)3·nH2O↓+1.5Na2SO4+1.5(NH4)2SO4.
[0050] 4. Aging The slurry obtained from the above reaction was transferred to an aging tank and aged for 4 hours.
[0051] 5. Washing The aged slurry is added into a centrifuge to remove the mother liquor, and then washed continuously at high speed with 45°C warm pure water until the pH of the washing water is detected to be below 8.
[0052] 6. Drying Put the washed qualified materials into the oven for drying at a temperature of 100°C and a drying time of 12-15 hours.
[0053] 7. Grinding The dried material was poured into a ball mill and ground until there was no agglomerate. After grinding, 10 kg of solid particles (with a water content of about 40%, including crystal water) were obtained.
[0054] 8. Mixing hot melt molding Take 4kg of polypropylene granules and 5kg of the above-ground powder, mix thoroughly and put them into a hot melt injection molding machine, melt them into a fluid state at 250℃. Pass compressed air through the extrusion hole to extrude them into cylindrical strips, and cut them into granular materials of Ф3mm×4mm.
[0055] 9. Product indicators and performance testing The lithium-aluminum ratio of the aluminum-based adsorbent powder prepared by this method is 1 mol:3 mol. After testing, the specific surface area of the aluminum-based adsorbent powder is 64.5 m 2 / g, tap density is 0.85g / cm3 When tested with 400ppm lithium-containing brine, the minimum adsorption capacity of the granular material was 4.1mg / g and the maximum adsorption capacity was 5.7mg / g.
[0056] Example 3 1. Preparation of raw materials and equipment Same as Example 1.
[0057] 2. Ingredients Prepare 15.00 L of aluminum sulfate solution with a metal ion concentration of 4 mol / L, prepare 5.00 L of lithium sulfate solution with a metal ion concentration of 7.2 mol / L. Prepare 20 L of aluminum sulfate and lithium sulfate mixed salt solution with a molar ratio of aluminum to lithium of 62.5%:37.5% and a total metal ion concentration of 4.8 mol / L (mass concentration: 4.8×19.465=93.4 g / L).
[0058] 3. Reaction Take 15L of qualified aluminum-lithium mixed salt solution and add it to the reactor, turn on the stirring at 180rpm, set the temperature to 80℃, and after the temperature reaches 90℃, introduce compressed air with a pressure of 0.3Mpa and a flow rate of 5L / h. At the same time, use a peristaltic pump to pass 20% ammonia water into the reactor at a flow rate of 5L / h. The ammonia water addition time is 6 hours, and the total amount of ammonia water added is 30L. The whole reaction is an exothermic process, during which the online pH gradually increases from 2.6 to 10.5. After adding ammonia water, adjust the pH. If the pH is not reached, add 10% sodium hydroxide to adjust it appropriately. The start time of the entire reaction starts from the addition of ammonia water. A white precipitate is produced after the addition of ammonia is completed. The stirring is increased to 240rpm, and the compressed air flow rate is not adjusted. Continue the reaction for 18 hours to obtain a slurry. After the reaction is completed, turn off the stirring, turn off the heating, and turn off the compressed air. The reaction equation is as follows: Al2(SO4)3+0.6Li2SO4+6NH3·H2O→0.6Li2SO4·2Al(OH)3·nH2O↓+2(NH4)2SO4(n=6).
[0059] 4. Aging The slurry obtained from the above reaction was transferred to an aging tank and aged for 6 hours.
[0060] 5. Washing The aged slurry is added into a centrifuge to remove the mother liquor, and then washed continuously at high speed with 45°C warm pure water until the pH of the washing water is detected to be below 8.
[0061] 6. Drying Put the washed qualified materials into the oven for drying at a temperature of 120°C and a drying time of 12-15 hours.
[0062] 7. Grinding The dried material was poured into a ball mill and ground until there was no agglomerate. After grinding, 13 kg of solid particles (with a water content of about 40%, including crystal water) were obtained.
[0063] 8. Mixing hot melt molding Take 4kg of polypropylene granules and 5kg of the above-ground powder, mix thoroughly and put them into a hot melt injection molding machine, melt them into a fluid state at 250℃. Pass compressed air through the extrusion hole to extrude them into cylindrical strips, and cut them into granular materials of Ф3mm×4mm.
[0064] 9. Product indicators and performance testing The lithium-aluminum molar ratio of the aluminum adsorbent powder prepared by this method is 62.5%:37.5%, and the lithium content is relatively normal. After testing, the specific surface area of the aluminum adsorbent powder is 46.1m 2 / g, tap density is 0.91g / cm 3 When tested with 400ppm lithium-containing brine, the minimum adsorption capacity of the granular material was 4.68mg / g and the maximum adsorption capacity was 6.04mg / g.
[0065] Example 4 1. Raw materials and equipment preparation Aluminum chloride, lithium chloride, ammonia water and polypropylene are used as raw materials. 100L reactor, feeding pump, small centrifuge, screening machine, mixer, hot melt injection molding machine, PPH storage tank and other equipment are used.
[0066] 2. Ingredients Prepare 15.00L of aluminum chloride solution with a metal ion concentration of 3.0mol / L and 5.00L of lithium chloride solution with a metal ion concentration of 5.0mol / L. After mixing the two metal salt solutions, add 10.00L of pure water to prepare 30.00L of aluminum sulfate and lithium sulfate mixed salt solution with a molar ratio of aluminum to lithium of 64%:36% and a total metal ion concentration of 3.2mol / L (mass concentration: 3.2×19.76=84.5g / L).
[0067] 3. Reaction Take 30L of qualified aluminum-lithium mixed salt solution and add it to the reactor, turn on the stirring at 180rpm, set the temperature to 80℃, and after the temperature reaches 80℃, introduce compressed air with a pressure of 0.3Mpa and a flow rate of 5L / h. At the same time, use a peristaltic pump to pass 20% ammonia water into the reactor at a flow rate of 5L / h. The ammonia water addition time is 6 hours, and the total amount of ammonia water added is 30L. The whole reaction is an exothermic process, during which the online pH gradually increases from 2.4 to 9.7. After adding ammonia water, adjust the pH. If the pH is not reached, add 10% concentration of sodium hydroxide to adjust it appropriately. The start time of the entire reaction starts from the addition of ammonia water. A white precipitate is produced after the addition of ammonia is completed. The stirring is increased to 240rpm, and the compressed air flow rate is not adjusted. Continue the reaction for 18 hours to obtain a slurry. After the reaction is completed, turn off the stirring, turn off the heating, and turn off the compressed air. The reaction equation is as follows: AlCl3+0.5LiCl+6NH3·H2O→0.5LiCl·Al(OH)3·nH2O↓+(NH4)Cl(n=6).
[0068] 4. Aging The slurry obtained from the above reaction was transferred to an aging tank and aged for 4 hours.
[0069] 5. Washing The aged slurry is added into a centrifuge to remove the mother liquor, and then washed continuously at high speed with 45°C warm pure water until the pH of the washing water is detected to be below 8.
[0070] 6. Drying Put the washed qualified materials into the oven for drying at 80℃ for 15-20h.
[0071] 7. Grinding The dried material was poured into a ball mill and ground until there was no agglomerate. After grinding, about 4.5 kg of solid particles (with a water content of about 40%, including crystal water) were obtained.
[0072] 8. Mixing hot melt molding Take 4kg of polypropylene granules and 4.5kg of the above-ground powder, mix them thoroughly and put them into a hot melt injection molding machine, introduce compressed air, and melt them into a fluid state at 250°C. After adding the mold and cooling, they are molded.
[0073] 9. Product indicators and performance testing The lithium-aluminum ratio of the aluminum-based adsorbent powder prepared by this method is 64%:36%. After testing, the specific surface area of the aluminum-based adsorbent powder is 70.9m 2 / g, tap density is 0.86g / cm 3 When tested with 400ppm lithium-containing brine, the minimum adsorption capacity of the granular material was 4.1mg / g and the maximum adsorption capacity was 5.9mg / g.
[0074] Example 5 The steps are similar to those in Example 1, except that the total concentration of metal ions in the mixed salt is 1.2 mol / L, and the molar ratio of lithium to aluminum ions is 25%:75%. The maximum amount of ammonia water used is 30 L, and the stirring speed is relatively low. The powder product is about 5 kg, with a specific surface area of 76.2 m2 / g and a tap density of 0.82 g / cm³. The product adsorption capacity is 4.3-5.8 mg / g.
[0075] Example 6 The steps are similar to those in Example 1, except that the metal ion concentration is doubled during batching, the total metal ion concentration of the mixed salt is 2.4 mol / L, and 20% sodium hydroxide solution is added during the reaction to adjust the pH. Due to the increased raw material concentration, the reaction speed is increased by 30rpm-60rpm, and the powder material output is doubled, from 5kg to 10kg. Due to the increased concentration, the amount of complexing agent remains unchanged, and the compressed air pressure and flow rate remain unchanged, so the specific surface area of the powder product decreases to 64.5m 2 / g. However, the adsorption amount of the products was not much different, the result was 4.1mg / g-5.7mg / g.
[0076] Example 7 The steps are similar to those in Example 1, except that the ratio of metal ions is adjusted to 62.5%:37.5% during batching, and the batching concentration is increased again, with the total concentration of metal ions in the mixed salt being 4.8 mol / L. As the concentration increases, more ammonia water is required for complexation. Limited by the size of the reactor, 20 L of mixed salt solution is taken to participate in the reaction. The flow rates of compressed air and ammonia water remain unchanged during the process, and the reaction speed is the same as that in Example 2. Compared with Examples 1 and 2, the reaction temperature is increased to 90°C. The output is relatively large, with a product output of 13 kg, so the drying temperature is increased to 120°C. As the concentration increases again, the amount of complexing agent remains unchanged, and the compressed air pressure and flow rate remain unchanged, so the specific surface area of the powder product drops to 46.1 m 2 / g, the corresponding tap density is increased to 0.91g / cm 3 Due to the increase in the proportion of lithium content, the adsorption capacity of the product increased slightly, and the result was 4.68mg / g-6.04mg / g.
[0077] Example 8 The steps are similar to those in Example 1, except that chloride salt is used as the raw material, the metal ion ratio is adjusted to 64%:36% during batching, and the total metal ion concentration of the mixed salt is 3.2 mol / L. The reaction speed, ammonia water and compressed air dosage remain unchanged. The drying temperature is reduced to 80°C, but the drying time is also increased. Finally, 4.55 kg of product is obtained. Experimental results: The specific surface area of the powder product is 70.9 m 2 / g, corresponding to a tap density of 0.86g / cm 3 The adsorption capacity in chlorinated brine is 4.1mg / g-5.9mg / g.
[0078] From the above results, it can be seen that in the preparation process of the aluminum-based adsorbent material for lithium extraction from salt lakes provided by the embodiment of the present invention, by controlling the reaction parameters within a suitable range, a aluminum-based adsorbent material for lithium extraction from salt lakes with a stable structure and high adsorption efficiency can be obtained. In addition, during the preparation process, due to the increase in concentration step, the relative compressed air flow rate decreases, the specific surface area of the product decreases, and the product tap density increases. It is not difficult to see that when the compressed air flow rate increases, the specific surface area of the product increases. The specific surface area of the product is 30m 2 / g-100m 2 / g, tap density 0.8g / cm 3 -1.2g / cm 3 However, the adsorption performance of the final products was not much different, all ranging from 4 mg / g to 6 mg / g.
[0079] As can be seen from the above, the embodiment of the present invention provides an aluminum-based adsorption material for lithium extraction from salt lakes. The aluminum-based adsorption material for lithium extraction from salt lakes provided by the present invention has a single adsorption property for lithium in different types of salt lakes, and has a large adsorption capacity. It can effectively separate other calcium, magnesium, iron, and boron ions in brine, and preferentially extract lithium ions. The extracted lithium salt has a small loss after elution and concentration, and a high yield. It has been concluded in practice that the theoretical adsorption capacity of 1 ton of granular material can reach 10kg of lithium ions. The actual test uses 400ppm lithium-containing brine to adsorb 4kg-6kg of lithium ions, and the adsorption rate is about 50%. The adsorption time of the test process is within 4 hours to 8 hours, and the elution time can also be controlled within 8 hours. The entire adsorption cycle is about 16 hours. The brine flow rate in the adsorption process is set to 0.5-1 times the filling volume of the granular material, and the eluent flow rate in the elution process is set to 1-2 times the volume of the granular material filling tower, which meets low flow rate adsorption and high flow rate elution. The adsorption and elution method has a large adsorption capacity, a short adsorption and elution cycle, and high adsorption efficiency.
[0080] According to the average annual production of 1,000 tons of adsorbent products by ordinary enterprises, the downstream salt lake lithium extraction can achieve an adsorption capacity of 6 tons of lithium per day (equivalent to 30 tons of lithium carbonate). While purifying brine, it also improves the efficiency of enterprises and reduces the production costs of downstream enterprises. It is estimated that the annual gross profit of enterprises with an annual production of 10,000 tons of lithium carbonate is 800 million to 1.2 billion yuan.
[0081] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A salt lake lithium aluminum adsorption material, characterized in that: The aluminum-based adsorbent material for lithium extraction from salt lakes is a composite of aluminum-based adsorbent powder and polymer material, wherein: the composition of the aluminum-based adsorbent powder is LiXAl(OH)3·nH2O, X is at least one of Cl, SO4, CO3, PO4, and NO3, and the mass ratio of the aluminum-based adsorbent powder to the polymer material is 1.0:(0.5-1.0).
2. The aluminum-based adsorption material for lithium extraction from salt lake according to claim 1, characterized in that: The high molecular polymer material is a thermoplastic material, and the thermoplastic material includes at least one of PP, PPS, PVC, PVDF, resin, glycolipid, phenolic resin, urea-formaldehyde resin, melamine resin, unsaturated polyester resin, epoxy resin, silicone resin, and polyurethane.
3. The aluminum-based adsorption material for lithium extraction from salt lake according to claim 1, characterized in that: The specific surface area of the aluminum adsorbent powder is 30 m 2 / g-100m 2 / g, tap density is 0.8g / cm 3 -1.2g / cm 3 .
4. The aluminum-based adsorption material for lithium extraction from salt lakes according to any one of claims 1 to 3, characterized in that: The lithium adsorption capacity of the aluminum-based adsorption material for lithium extraction from salt lakes is 4.3 mg / g-5.8 mg / g, and the salt lake type includes at least one of a lithium chloride salt lake, a lithium sulfate salt lake, and a lithium carbonate salt lake.
5. A method for preparing aluminum-based adsorption materials for lithium extraction from salt lakes according to any one of claims 1 to 4, characterized in that: It includes: The mixed salt solution of aluminum and lithium and the complexing agent solution are mixed to carry out complex precipitation reaction, and the aluminum-based adsorbent powder is obtained after treatment. The aluminum-based adsorbent powder is mixed with the polymer material and then heat-melted into a fluid state, and then extruded or granulated with a mold, and the lithium ions are circulated and eluted with an eluent to obtain the aluminum-based adsorbent material for lithium extraction from salt lakes.
6. The preparation method according to claim 5, characterized in that: The preparation of the aluminum adsorbent powder comprises: adding a mixed salt solution of aluminum salt and lithium salt into a reactor, starting stirring and heating, introducing compressed air with a pressure of 0.2MPa-0.4MPa and a flow rate of 1 / 30-1 / 10 of the volume of the reactor into the bottom of the mixed salt solution, then continuously and constantly introducing the complexing agent solution into the reactor for precipitation reaction, controlling the flow rate of the complexing agent solution to be 1 / 30-1 / 10 of the volume of the reactor, controlling the pH at 1.0-4.0 in the early stage of the precipitation reaction, controlling the pH at 4-8 in the middle stage, and controlling the pH at 8-12 in the late stage, adding a pH regulator to adjust the pH during the pH adjustment process, and obtaining a slurry after the precipitation reaction is completed, wherein: The aluminum salt includes at least one of aluminum sulfate, aluminum carbonate, aluminum chloride, aluminum silicate, and aluminum nitrate; the lithium salt includes at least one of lithium sulfate, lithium carbonate, and lithium chloride; the complexing agent includes at least one of ammonia water, urea, and sodium hydroxide; and the pH adjuster includes at least one of dilute sulfuric acid, dilute hydrochloric acid, dilute nitric acid, and dilute alkali; The total concentration of aluminum and lithium metal ions in the mixed salt solution is 1.0 mol / L-5.0 mol / L, and the proportion of lithium metal in the metal ions is 20%-60%. The stirring speed of the mixed salt solution is 100 rpm-300 rpm, the heating temperature is 70°C-90°C, the concentration of the complexing agent solution is 10%-20%, the ratio of the amount of metal ion substance to the amount of the complexing agent substance in the mixed salt solution is 1:(5-15), and the concentration of the pH regulator is 10%-30%.
7. The preparation method according to claim 6, characterized in that: Also includes: The slurry obtained by the reaction is aged for 4h-6h, then washed with warm water at 40℃-60℃ until it is neutral, dried at 80℃-120℃ until the moisture content of the material is ≤40%, and then the dried material is ground to a maximum particle size of ≤50um to obtain an aluminum-based adsorbent powder.
8. The preparation method according to claim 5, characterized in that: The preparation of the aluminum-based adsorption material for lithium extraction from salt lakes includes: mixing the aluminum-based adsorbent powder and the high molecular polymer material in a mass ratio of 1.0:(0.5-1.0) to obtain a mixed material, then introducing compressed air with a pressure of 0.2MPa-0.4MPa, a temperature of 80°C-120°C, and a flow rate of 1 / 20-1 / 10 of the volume of each batch of the mixed material into the mixed material, then hot-melting at ≤300°C to obtain a fluid material, then extruding the fluid material into a mold or granulating it into a porous and loose granular material, and cyclically eluting the porous and loose granular material with an eluent to remove lithium ions, thereby obtaining the aluminum-based adsorption material for lithium extraction from salt lakes.
9. Use of the aluminum-based adsorption material for lithium extraction from salt lakes according to any one of claims 1 to 4 or the aluminum-based adsorption material for lithium extraction from salt lakes prepared by the preparation method of any one of claims 5 to 8 in lithium extraction from salt lakes.
10. The use according to claim 9, characterized in that: During the lithium extraction and adsorption process from the salt lake, the brine flow rate is 0.5 to 1 times the volume of the tower filled with the aluminum-based adsorption material for lithium extraction from the salt lake, and the eluent flow rate during the elution process is 1 to 2 times the volume of the tower filled with the aluminum-based adsorption material for lithium extraction from the salt lake.
Citation Information
Cited By
A method and process system for efficient lithium extraction and resource utilization from low- to medium-grade lithium-containing brines
CN121342055B